Age and sex identification from wings of sage‐grouse - Clait E. Braun; Michael A. Schroeder (Wildlife Society Bulletin)
ABSTRACT We redefine and clarify procedures to classify sex and age (juveniles, yearlings, adults, and breeding‐age) of greater (Centrocercus urophasianus) and Gunnison sage‐grouse (C. minimus) from wings. Existing keys for greater sage‐grouse age and sex classification do not incorporate more recent information on timing and sequence of molt or regional variation. We evaluated keys with the aid of gonadally inspected, hunter‐harvested sage‐grouse in Colorado (1973–1990) and with birds captured and measured in Washington (1992–1997) and Oregon (2008–2012). The technique is accurate and transferable among biologists who have basic training in reading a key and examining wings (primaries, secondaries, tertials, and coverts). Accurate information on sex and age of grouse, particularly during harvest, is a fundamental component of our understanding of population dynamics, which ultimately enables improved management. © 2014 The Wildlife Society.